2002
DOI: 10.1577/1548-8659(2002)131<0931:lhaofa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Life History Attributes of Fishes along the Latitudinal Gradient of the Missouri River

Abstract: Populations of two short-lived species (emerald shiner Notropis atherinoides and sicklefin chub Macrhybopsis meeki) and three long-lived species (freshwater drum Aplodinotus grunniens, river carpsucker Carpiodes carpio, and sauger Stizostedion canadense) were studied in the Missouri River to examine spatial variations in life history characteristics across a latitudinal and thermal gradient (38Њ47ЈN to 48Њ03ЈN). The life history characteristics included longevity (maximum age), the rate at which asymptotic len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 49 publications
(82 reference statements)
4
41
0
Order By: Relevance
“…The temperature slopes (␤) estimated for these species did not change significantly when mass was excluded from the regression in all cases except Stizostedion canadense. Importantly, this species is also known to exhibit a latitudinal gradient in the genetic capacity for growth (30), which can potentially generate an interaction between the effects of temperature and mass that is not accounted for in standard MTE analyses. All subsequent results refer to regressions including only temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature slopes (␤) estimated for these species did not change significantly when mass was excluded from the regression in all cases except Stizostedion canadense. Importantly, this species is also known to exhibit a latitudinal gradient in the genetic capacity for growth (30), which can potentially generate an interaction between the effects of temperature and mass that is not accounted for in standard MTE analyses. All subsequent results refer to regressions including only temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Winemiller and Rose (1992) reported that cyprinids are typically small-bodied fishes with a short lifespan and that longevity of fishes in the family is less than all other North American families. Short life spans are particularly common in cyprinids native to the Great Plains (e.g., Guy 2001, Braaten andGuy 2002). Like growth and mortality, understanding patterns in recruitment is important for better understanding the life history of fishes and potential effects of disturbance on fish population dynamics.…”
Section: Data Anafysismentioning
confidence: 99%
“…Latitudinal increases in water temperature, degreedays, and the duration of the growing season from north to south have been associated with changes in life history traits such as growth, mortality, and longevity (Beamesderfer and North 1995;Lobón-Cerbiá et al 1996;Braaten and Guy 2002). Studies of European eel have shown that, although differentiation of the gonads takes place during the yellow stage (Colombo and Grandi 1996), the growth rate of elvers during their first year of life emerges as a strong predictor of subsequent gender with males growing faster than females in the early stages (Holmgren et al 1997).…”
Section: Temperaturementioning
confidence: 99%
“…Life history attributes of fishes along latitudinal gradients indicate that, within a species, longevity increases and mortality decreases from south to north (Colby and Nepzy 1981;Beverton 1987;Braaten and Guy 2002), that body size increases from south to north (Winemiller 1991;Taylor and Gotelli 1994), and that growth rates (as indicated by the Von Bertalanffy growth coefficient k) increase from north to south (Beverton 1987;Lobón-Cerbiá et al 1996;Braaten and Guy 2002). Trade-offs between longevity and mortality produce differential…”
Section: Filling Information Gapsmentioning
confidence: 99%
See 1 more Smart Citation